Oil on water : a novel - Helon Habila (: Penguin Books, 2011)
From the desks of Nigeria's newsrooms, two journalists are recruited to find the kidnapped wife of a British oil engineer. Zaq, an infamous media hack, knows what's in store, but Rufus, a keen young journalist eager to get himself noticed, has no idea what he's let himself in for.